PENEGAKAN HUKUM DALAM MENANGGULANGI TINDAK PIDANA PEREDARAN MAKANAN KEMASAN YANG TIDAK MEMILIKI IZIN EDAR DI PROVINSI RIAU - Ambarita, Agustin Pratiwi; Deliana, Evi; ', Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Food packaging that does not have a marketing authorization will threaten the health and safety of consumers because there is no guarantee of the safety and nutritional quality of the Food and Drug Supervisory Agency. Therefore, it is important that circulation permits issued by the government through prevent the occurrence of imported food packaging that threatens the health of consumers. Therefore, in Article 37 paragraph (1) of Law No. 18 of 2012 on Food states that every domestic food import must meet the requirements of security, quality, nutrition and not contrary to religion, belief and culture of society. However, in reality there are still many packaging foods that do not have distribution permit in the community. The research formulation of this thesis that is: first, How law enforcement against the circulation of food packaging that does not have distribution authorization in Riau Province? Secondly, What are the constraints of law enforcement efforts on the circulation of food packaging packaging that does not have distribution authorization in Riau Province? Thirdly, how is the effort to overcome the obstacle of law enforcement on the circulation of food packaging that does not have distribution license in Riau Province?The method of sociological juridical research, because in this study the authors directly procure research on the location and place studied in order to provide a complete and clear picture of the problem under study. This research was conducted and some shops selling packaged food which did not have circulation permit, while the population and sample were all parties related to the problem studied in this research. Sources of data used, primary and secondary data, and tertiary data, data collection techniques in this study with questionnaires, interviews, and literature review.The results of the study there are three points inferred. Firstly, law enforcement conducted Pekanbaru has not run optimally. This is because the Food and Drug Supervisory Agency Pekanbaru less intensity in conducting surveillance, so it is still found traders who sell food packaging that does not have a marketing authorization and light sanctions given to the perpetrator. Second, the constraints of external and internal factors. Third, the Food and Drug Supervisory Agency Pekanbaru effort to overcome the obstacles faced in overcoming the circulation of packaged food that does not have distribution license, additional employees, sanction and socialization of Consumer Complaint Service Unit Suggestion Writer: First more optimal supervision, Second improve cooperation with related parties, the third increases the roleKeywords: Law Enforcement-Permit Food Delivery Packaging